Strigolactone Levels in Dicot Roots Are Determined by an Ancestral Symbiosis-Regulated Clade of the PHYTOENE SYNTHASE Gene Family - Stauder, Ron; Welsch, Ralf; Camagna, Maurizio; Kohlen, Wouter; Balcke, Gerd U.; Tissier, Alain; Walter, Michael H. (Frontiers in Plant Science, 2018)
Strigolactones are apocarotenoid phytohormones synthesized from carotenoid precursors. They are produced most abundantly in roots for exudation into the rhizosphere to cope with mineral nutrient starvation through support of root symbionts. Abscisic acid (ABA) is another apocarotenoid phytohormone synthesized in roots, which is involved in responses to abiotic stress. Typically low carotenoid levels in roots raise the issue of precursor supply for the biosynthesis of these two apocarotenoids in this organ. Increased ABA levels upon abiotic stress in Poaceae roots are known to be supported by a particular isoform of PHYTOENE SYNTHASE (PSY), catalyzing the rate-limiting step in carotenogenesis. Here we report on novel PSY3 isogenes from Medicago truncatula (MtPSY3) and Solanum lycopersicum (SlPSY3) strongly expressed exclusively upon root interaction with symbiotic arbuscular mycorrhizal (AM) fungi and moderately in response to phosphate starvation. They belong to a widespread clade of conserved PSYs restricted to dicots (dPSY3) distinct from the Poaceae-PSY3s involved in ABA formation. An ancient origin of dPSY3s and a potential co-evolution with the AM symbiosis is discussed in the context of PSY evolution. Knockdown of MtPSY3 in hairy roots of M. truncatula strongly reduced strigolactone and AM-induced C13 alpha-ionol/C14 mycorradicin apocarotenoids. Inhibition of the reaction subsequent to phytoene synthesis revealed strongly elevated levels of phytoene indicating induced flux through the carotenoid pathway in roots upon mycorrhization. dPSY3 isogenes are coregulated with upstream isogenes and downstream carotenoid cleavage steps towards strigolactones (D27, CCD7, CCD8) suggesting a combined carotenoid/apocarotenoid pathway, which provides “just in time”-delivery of precursors for apocarotenoid formation.